2015
DOI: 10.1021/acs.macromol.5b00806
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Level of Intermacromolecular Interactions in Ethylene–Propylene Copolymers by Using Pyrene Excimer Formation

Abstract: A unique methodology based on fluorescence measurements is introduced to quantitatively measure the actual level of interpolymeric association between ethylene-propylene (EP) copolymers used as viscosity index improvers (VIIs) in engine oils. To this end, two EP copolymers, one amorphous (EP(AM)) and the other semicrystalline (EP(SM)), were maleated and then fluorescently labeled with 1-pyrenemethylamine and 2-(2-naphthyl)ethylamine to yield increased upon decreasing the temperature and increasing the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…As for EP(80) in Figure , this behavior was attributed to the formation of crystalline microdomains by EP(78) in toluene that would lead to an enhancement of [ Py ] loc and thus of the I E / I M ratio. This feature of the I E / I M ‐vs‐ T profiles seems to be common for semicrystalline polymers randomly labeled with pyrene …”
Section: Characterization Of Polymeric Oil Additives By Pefmentioning
confidence: 66%
See 3 more Smart Citations
“…As for EP(80) in Figure , this behavior was attributed to the formation of crystalline microdomains by EP(78) in toluene that would lead to an enhancement of [ Py ] loc and thus of the I E / I M ratio. This feature of the I E / I M ‐vs‐ T profiles seems to be common for semicrystalline polymers randomly labeled with pyrene …”
Section: Characterization Of Polymeric Oil Additives By Pefmentioning
confidence: 66%
“…The four I E / I M ‐vs‐ T profiles shown in Figure were processed according to eq to yield plots of f inter as a function of temperature for the two PMA‐EP(60) and PMA‐EP(78) samples at a polymer concentration of 10 g L −1 . Similar experiments were conducted for the same Py‐EP copolymers at a polymer concentration of 10 mg L −1 and the corresponding f inter values were also included in Figure . Contrary to the complex behavior of the I E / I M trends observed in Figure , the f inter ‐vs‐ T profiles shown in Figure could be readily interpreted.…”
Section: Characterization Of Polymeric Oil Additives By Pefmentioning
confidence: 80%
See 2 more Smart Citations
“…Huser et al 50 studied the several types of aggregates in films cast from solutions of distinct solvents, which are the reason for the multicolored fluorescence they observed. Also, Duhamel et al [51][52][53][54] demonstrated that intermolecular interactions can be quantitatively described by steady-state and time-resolved fluorescence spectroscopy, since the distinct aggregates present distinct photophysics. Vol.…”
mentioning
confidence: 99%